Perancangan dan Dokumentasi Pembangunan Ruang Kelas TK Salsabilla di Desa Pematang Serai, Kabupaten Langkat - Sagala, Peranita; Wisdianti, Dara; Novalinda, Novalinda; Siregar, Ardiansyah; Rambe, Ivan Noor Akbar (PT. Arsil Reka Engineering, 2024)
Early childhood education requires a learning environment that is safe, comfortable, engaging, and responsive to children's characteristics. Salsabila Kindergarten in Pematang Serai Village, Tanjung Pura District, Langkat Regency, is one such facility requiring a learning space that adequately supports children's educational activities. This community service activity aimed to develop a classroom design suited to early childhood learning needs and to document the building's condition after construction. The method involved a design process and consultation with the kindergarten management in 2010, with the resulting design later used as a reference for construction. In 2023, documentation was carried out on the completed and functioning building. Results show that the proposed design was successfully implemented while retaining its key characteristics, including a symmetrical façade composition, geometric forms, bright colors, an emphasized entrance area, and openings through doors and windows. Post-construction observations indicate that the classroom is actively used as a learning facility, equipped with supporting materials for children's activities. These findings demonstrate that architectural design considering both function and user characteristics can help create a more engaging and appropriate learning environment for early childhood education.